State and Evolution of Public and Private Research and Development in Bulgarian Agriculture - Bachev, Hrabrin (International Journal of Sustainable Development & World Policy, 2020)
Despite the great theoretical and practical significance, in Bulgaria there are no comprehensive analysis of the state and evolution of agrarian research and development (ARD) activities in public and private sectors. The goal of this paper is to analyze the state and evolution of ARD in Bulgaria during the period after country’s EU accession in 2007, identify major trends in that area, make a comparison with other EU states, specify main problems, and suggest conclusions for improvement of policies during next programing period. The analysis has found out that in years of EU membership the expenditures for ARD significantly decreased absolutely and relatively as a share in the total expenditures for R&D, which indicates diminishing importance, and deteriorating financial, personnel and material potential of agrarian knowledge and innovation sector. The most important sector for ARD in the country is the government in which more than 80% of overall expenditures for ARD are invested, as distribution of expenditures and organization of R&D in major sectors differ considerably from other EU member states. ARD in the country mainly are funded by the state budget, and the importance of budget financing relatedly increases during the period, unlike trends in other EU countries.